A multifaceted intervention to increase prophylactic oxytocin use during the third stage of labor and to reduce routine episiotomies in Nicaragua. Issue 1 (19th June 2014) - García‐Elorrio, Ezequiel; Aleman, Alicia; Cafferata, Maria L.; Colomar, Mercedes; Tomasso, Giselle; Lacayo, Yann; Espinoza, Henry; Villadiego, Shirley; Engelbrecht, Susheela; Althabe, Fernando
Abstract: Objective: To assess the effect of a multifaceted intervention among skilled birth attendants on the use of oxytocin during the third stage of labor, the active management of the third stage of labor (AMTSL), and the rate of routine episiotomy during vaginal births in two health districts in Nicaragua. Methods: An uncontrolled before‐and‐after study design was used. The rates of oxytocin use in the third stage of labor, AMTSL, and episiotomy were measured for vaginal births occurring in eight hospitals and health centers during 2011–2012, before and after implementation of a multifaceted facility‐based intervention. The intervention involved the use of opinion leaders, interactive workshops to develop and implement evidence‐based guidelines, academic detailing, the use of reminders, and feedback on the rates of oxytocin use and episiotomy. Results: Oxytocin use during the third stage of labor increased significantly from 95.3% to 97.4% (P = 0.003). The episiotomy rate dropped significantly from 31.2% to 21.2% overall, and from 59.6% to 40.5% in primiparous women (P < 0.001 for both comparisons). Conclusion: The multifaceted intervention improved the targeted care practices during childbirth. However, a further decrease in the routine use of episiotomy would be desirable.